Nanolithographic Top-Down Patterning of Polyoxovanadate-based Nanostructures with Switchable Electrical Resistivity - Rösner, Benedikt; Fallica, Roberto; Johnson, Manuel; Späth, Andreas; Fink, Rainer; Ekinci, Yasin; David, Christian; Anjass, Montaha H.; Streb, Carsten (ChemNanoMat, 2020)
The top-down lithographic fabrication of functional metal oxide nanostructures enables technologically important applications such as catalysis and electronics. Here, we report the use of molecular vanadium oxides, polyoxovanadates, as molecular precursors for electron beam lithography to obtain functional vanadium oxide nanostructures. The new resist class described gives access to nanostructures with minimum dimensions close to 10 nm. The lithographically prepared structures exhibit temperature-dependent switching behaviour of their electrical resistivity. The work could lay the foundation for accessing functional vanadium oxide nanostructures in the sub-10-nm domain using industrially established nanolithographic methods.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Metal Oxide; Nanostructure; Polyoxometalates; Self-Assembly; Vanadium Oxide